The Effectiveness of BESAN (Bulletin on Marriage Age Maturation) on Knowledge, Perception and Behavior of Early Marriage Prevention in Adolescents - Ridawati, Indah Dewi; Aisyah, Aisyah; Wahyuni, Elly; Baska, Dwie Yunita (Asian Journal of Healthcare Analytics, 2024)
One of the factors causing early marriage is the lack of information received by teenagers. The purpose of this study was to determine the effect of BESAN (Buletin Penmasaan Usia Pernikahan) on knowledge, perception and behavior of maturing age of marriage. This type of research is a quasi-experiment with a pre-post without control group design. Samples were taken by accidental sampling of 113 teenagers. The results showed a significant increase in knowledge, perception and behavior of maturing marriage after using the bulletin, p = 0.000 (p <0.05).